2014
DOI: 10.1038/bjc.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumour growth by orally administered osteopontin is accompanied by alterations in tumour blood vessels

Abstract: Background:The integrin-binding protein osteopontin is strongly associated with tumour development, yet is an abundant dietary component as a constituent of human and bovine milk. Therefore, we tested the effect of orally administered osteopontin (o-OPN) on the development of subcutaneous tumours in mice.Methods:Bovine milk osteopontin was administered in drinking water to tumour-bearing immune-competent mice. Tumour growth, proliferation, necrosis, apoptosis and blood vessel size and number were measured. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…However, these sites are most likely protected by nearby posttranslational modifications such as phosphorylations, and as shown in this study, glycosylated OPN has been shown to resist proteolysis with neonatal gastric aspirates at pH 3.0 for 1 h at 37°C (Chatterton et al, 2004). As well, OPN has been shown to resist digestion in vivo in mice fed OPN by gavage or solubilized in chocolate milk (da Silva et al, 2009;Rittling et al, 2014). Bovine OPN was also detected in the plasma of human infants fed formula supplemented with bovine milk OPN (Jiang and Lönnerdal, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…However, these sites are most likely protected by nearby posttranslational modifications such as phosphorylations, and as shown in this study, glycosylated OPN has been shown to resist proteolysis with neonatal gastric aspirates at pH 3.0 for 1 h at 37°C (Chatterton et al, 2004). As well, OPN has been shown to resist digestion in vivo in mice fed OPN by gavage or solubilized in chocolate milk (da Silva et al, 2009;Rittling et al, 2014). Bovine OPN was also detected in the plasma of human infants fed formula supplemented with bovine milk OPN (Jiang and Lönnerdal, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…While trust was not specifically addressed in the focus groups, some participants mentioned that returning study findings could increase one's likelihood to recommend participating in research. Given the multitude of well-known, documented disparities in research participation [22][23][24][25][26][27], disseminating research results to participants could be one meaningful way to build trust and encourage future research participation [6,9,10,28,29]. Future research should assess how returning study findings impacts participants' trust and likelihood of participating in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have indicated that human and bovine milk OPN are in part resistant to proteolysis in the infant intestinal tract, which makes OPN a potentially bioactive component of human milk [ 108 ]. In animal studies after oral application of OPN some proteolytic cleavage products or even intact OPN could be detected in plasma using antibodies raised against OPN [ 109 , 110 ] and these peptides show biological effects [ 110 ].…”
Section: Human Milk Proteins With Bioactivitymentioning
confidence: 99%